Blood and urine biomarkers of disease progression in IgA nephropathy - Zhi-Yu Duan; Chun Zhang; Xiang-Mei Chen; Guang-Yan Cai (BMC, 2024)
Abstract The prognosis of patients with IgA nephropathy (IgAN) is variable but overall not good. Almost all patients with IgAN are at risk of developing end-stage renal disease within their expected lifetime. The models presently available for prediction of the risk of progression of IgAN, including the International IgA Nephropathy Prediction Tool, consist of traditional clinical, pathological, and therapeutic indicators. Finding biomarkers to improve the existing risk prediction models or replace pathological indicators is important for clinical practice. Many studies have attempted to identify biomarkers for prediction of progression of IgAN, such as galactose-deficient IgA1, complement, a spectrum of protein biomarkers, non-coding RNA, and shedding cells. This article reviews the biomarkers of progression of IgAN identified in recent years, with a focus on those with clinical value, in particular the combination of multiple biomarkers into a biomarker spectrum. Future research should focus on establishing a model based primarily on biomarkers that can predict progression of IgAN and testing it in various patient cohorts.